THE EFFECT OF THE INDIVIDUAL AND FAMILY SELF-MANAGEMENT PROMOTING PROGRAM ON FUNCTIONAL CAPACITY AMONG OLDER PERSONS WITH HIP FRACTURE - Rattanathummawat, Thanaporn; Choowattanapakorn, Tassana (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2018)
The purpose of this quasi-experimental research was to test the effect of the individual and family self-management promoting program on functional capacity among older persons with hip fracture. Purposive sampling was used to recruit 44 older persons with hip fracture admitted at orthopaedic ward, Police General Hospital. They were equally assigned into an experimental group and a control group matched by age, sex and type of operation. The instruments were the individual and family self-management promoting program based on Ryan & Sawin theory. The functional capacity measured by six-minute walk test (6MWT). The data were analyzed by mean, percentage, standard deviation, and t-test. The result showed that the mean score of functional capacity of older persons with hip fracture after receiving the individual and family self-management promoting program was significantly higher than the control group at p<.05. ( t=2.394, p=.021)